2014
DOI: 10.1186/1475-2875-13-360
|View full text |Cite
|
Sign up to set email alerts
|

Increased malaria transmission around irrigation schemes in Ethiopia and the potential of canal water management for malaria vector control

Abstract: BackgroundIrrigation schemes have been blamed for the increase in malaria in many parts of sub-Saharan Africa. However, proper water management could help mitigate malaria around irrigation schemes in this region. This study investigates the link between irrigation and malaria in Central Ethiopia.MethodsLarval and adult mosquitoes were collected fortnightly between November 2009 and October 2010 from two irrigated and two non-irrigated (control) villages in the Ziway area, Central Ethiopia. Daily canal water r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
81
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(91 citation statements)
references
References 28 publications
6
81
4
Order By: Relevance
“…ese further corroborate the impact of the dam on the persistence of Plasmodium infections during the dry season and hence malaria transmission. Similar findings of increased risk of malaria within irrigated areas elsewhere in Africa have been reported previously [36][37][38]. Construction of dams for irrigation and hydroelectricity to promote socioeconomic development in Africa has been projected to increase [39], but persistent malaria transmission could be an unintended consequence in these communities if adequate control measures are not implemented.…”
Section: Discussionsupporting
confidence: 76%
“…ese further corroborate the impact of the dam on the persistence of Plasmodium infections during the dry season and hence malaria transmission. Similar findings of increased risk of malaria within irrigated areas elsewhere in Africa have been reported previously [36][37][38]. Construction of dams for irrigation and hydroelectricity to promote socioeconomic development in Africa has been projected to increase [39], but persistent malaria transmission could be an unintended consequence in these communities if adequate control measures are not implemented.…”
Section: Discussionsupporting
confidence: 76%
“…Malaria risk increases with decreasing distance to irrigated areas, which are suitable mosquito breeding habitats and hence can be used as an internal tool to validate analyses . Our model showed that a 10% increase in the extent of irrigated areas increased malaria risk by almost 39% in the entire study area and by almost 44% within the 2‐km buffer of the selected villages.…”
Section: Discussionmentioning
confidence: 85%
“…This is due to changes in ecological and hydrological conditions that lead to increased vector abundance (Baeza et al, 2013). Kibret et al (2014), who revealed that the irrigation schemes intensify malaria transmission due to poor water management in irrigation areas, support this theory.…”
Section: Data Pre-processing: Creating Continuous Surfacesmentioning
confidence: 87%